2023
DOI: 10.1186/s12951-023-01903-5
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas13a-powered electrochemical biosensor for the detection of the L452R mutation in clinical samples of SARS-CoV-2 variants

Abstract: Since the end of 2019, a highly contagious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has deprived numerous lives worldwide, called COVID-19. Up to date, omicron is the latest variant of concern, and BA.5 is replacing the BA.2 variant to become the main subtype rampaging worldwide. These subtypes harbor an L452R mutation, which increases their transmissibility among vaccinated people. Current methods for identifying SARS-CoV-2 variants are mainly based on polymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…195 Electrochemical sensors for microorganisms using MXene-based nanomaterials are summarized in Table 4. Exosomes, 196–199 bacteria, 200–205 viruses, 149,206–209 and even cancer cells 114,171 can be measured through appropriate surface modification of electrodes. The lowest sensing range is about 10 particles per μL.…”
Section: The Applications Of Mxenes In Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…195 Electrochemical sensors for microorganisms using MXene-based nanomaterials are summarized in Table 4. Exosomes, 196–199 bacteria, 200–205 viruses, 149,206–209 and even cancer cells 114,171 can be measured through appropriate surface modification of electrodes. The lowest sensing range is about 10 particles per μL.…”
Section: The Applications Of Mxenes In Biosensorsmentioning
confidence: 99%
“…194 Chen et al used electrodes made of MXene–AuNP composites for improved sensitivity and the CRISPR/Cas13a system for high specificity in detecting the single-base L452R mutation (in the SARS-Cov-2 virus) in RNAs and clinical samples. 208 Kim et al developed a field-ready cyanobacterial pretreatment device and an electrochemical clustered regularly interspaced short palindromic repeats (EC-CRISPR) biosensor. 200 The biosensor was composed of CRISPR/Cpf1 protein conjugated with MXene on an Au microgap electrode (AuMGE) integrated into a printed circuit board (PCB).…”
Section: The Applications Of Mxenes In Biosensorsmentioning
confidence: 99%
“…Single-nucleotide variations (SNVs), as the genetic basis of many diseases related to susceptibility and individual response to therapy, are significant biomarkers in not only biological research but also pharmacology, disease diagnosis, and population genetics in the postgenomic era. [1][2][3][4][5][6] Genome-wide association studies have identified SNVs associated with diverse human illnesses, such as cancer, neurodegenerative disease, cardiovascular disease, reaction (PCR, 1-2 h), reverse transcriptase droplet digital PCR (RT-ddPCR, ≈24 h), isothermal amplification (0.5-1 h), CRISPR-Cas (0.5-2 h), colorimetric assay [15] (≈0.5 h), electrochemistry [27] (≈45 min) and so on. However, to realize sensitive SNV detection, these methods normally require nucleic acid amplification, which increases operational complexity and takes tens of minutes to obtain the result.…”
Section: Introductionmentioning
confidence: 99%
“…One of the key mutations of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), spike L452R (corresponding to single-nucleotide variant T22917G), is synthesized as our target sequence (i.e., target input, TAR), which was reported to be associated with an increased viral infectivity 30,31 and was used to track the pandemic. 32 A highly conserved SARS-CoV-2 sequence (belonging to ORF1ab coding region, NSP6 gene) is synthesized as our reference input (REF). 33 As one of the inputs for the AND-logic gate, REF can be regarded as an internal reference and positive control for TAR detection, which can potentially increase the sensing specificity and lower the risk of false-positive results.…”
mentioning
confidence: 99%
“…Herein, we demonstrate a homogeneous AND-logic cascade RCA strategy for single-nucleotide variant discrimination and the real-time analysis of dual target nucleic acid sequences. One of the key mutations of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), spike L452R (corresponding to single-nucleotide variant T22917G), is synthesized as our target sequence (i.e., target input, TAR), which was reported to be associated with an increased viral infectivity , and was used to track the pandemic . A highly conserved SARS-CoV-2 sequence (belonging to ORF1ab coding region, NSP6 gene) is synthesized as our reference input (REF) .…”
mentioning
confidence: 99%